Service Quality Analysis of BPR XYZ - Ulfa Chusnia Wahyunita; Dwi Sukma Donoriyanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
BPR XYZ is a banking company engaged in savings, deposit, and loan services. In providing services to customers, its employees follow service standards established by the company. However, in reality, there are still many complaints from customers. Therefore, it is necessary to measure the quality of the services provided to determine whether they meet customer expectations and identify areas for improvement. This must be addressed immediately if the company wishes to remain competitive. This study will use the Service Quality (Servqual) method to address the issues faced. The Servqual method is used to measure the quality of service based on attributes of each dimension, resulting in a gap value that indicates the difference between consumer perceptions of the services received and their expectations of what should be received. This study evaluates 21 attributes, covering both service and product attributes offered. The results show that 12 attributes exceed customer expectations, including strategic location, availability of queue numbers, appropriate operating hours, clear and easy-to-understand information, assistance from officers when customers face issues, trustworthiness, the bank’s ability to ensure customer data security, confidentiality of customer data, non-discrimination, and understanding of customer needs. However, there are still 9 attributes below customer expectations, including the comfort of the waiting room, sufficient parking area, ease of transactions, reliability in resolving customer issues, waiting time, service speed, responsiveness to customer complaints, politeness in service, and the overall impression given to customers by the service provided.